2018
DOI: 10.1093/ajcn/nqx013
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of dietary ω-6 polyunsaturated fatty acids for saturated fatty acids decreases LDL apolipoprotein B-100 production rate in men with dyslipidemia associated with insulin resistance: a randomized controlled trial

Abstract: Background:The substitution of omega (ω)-6 (n-6) polyunsaturated fatty acids (PUFAs) for saturated fatty acids (SFAs) is advocated in cardiovascular disease prevention. The impact of this substitution on lipoprotein metabolism in subjects with dyslipidemia associated with insulin resistance (IR) remains unknown. Objective: In men with dyslipidemia and IR, we evaluated the impact of substituting ω-6 PUFAs for SFAs on the in vivo kinetics of apolipoprotein (apo) B-containing lipoproteins and on the intestinal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…The expression of the housekeeping gene glucose-6-phosphate-dehydrogenase (G6PD) was used as a reference. The intestinal expressions of ACS1 and SAR1B were quantified in n ϭ 95 and n ϭ 84 subjects, respectively, whereas the expressions of SREBP1c, FATP4, FABP2, ACS1, DGAT1, DGAT2, The validity of the intestinal gene expression model used in the present study was demonstrated in previous studies by the interrelationship of the expression of coregulated genes (5,9,10,39,41,42). The validity of the intestinal gene expression model is also supported by positive associations between the expression of the gene and the mass of the protein in biopsy samples, as previously reported (5,42).…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…The expression of the housekeeping gene glucose-6-phosphate-dehydrogenase (G6PD) was used as a reference. The intestinal expressions of ACS1 and SAR1B were quantified in n ϭ 95 and n ϭ 84 subjects, respectively, whereas the expressions of SREBP1c, FATP4, FABP2, ACS1, DGAT1, DGAT2, The validity of the intestinal gene expression model used in the present study was demonstrated in previous studies by the interrelationship of the expression of coregulated genes (5,9,10,39,41,42). The validity of the intestinal gene expression model is also supported by positive associations between the expression of the gene and the mass of the protein in biopsy samples, as previously reported (5,42).…”
Section: Methodsmentioning
confidence: 56%
“…The present study is a cross-sectional analysis of data from 127 male subjects who participated in intestinal gene expression studies in our laboratory (5,9,10,39,41,42). These studies were approved by the Laval University Ethical Review Committee, and written consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a cross-sectional analysis of data from male subjects who participated in in vivo tracer kinetic studies in our laboratory (22)(23)(24)(25)(26)(27)(28)(29)(30). Only data from subjects who were either on no particular treatment (22,28), a control diet (26,27,29), or on a placebo (23)(24)(25)30) in the previous studies were used for the present analyses. These studies were approved by the Laval University Ethical Review Committee, and written consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…31 A diet rich in omega-6 fatty acids is associated with a decrease in HDL-C and LDL-C production. 32 These fatty acids are more susceptible to oxidation and are therefore more atherogenic than oleic acid. In consequence, it is recommended that the diet of hypercholesterolemic children should include only a moderate amount of polyunsaturated fatty acids (7-10% of total energy), mainly in the form of vegetable oils, such as corn and sunflower seed oils.…”
Section: Intake Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%